A Comparative Analysis of Fuel Efficiency and Operational Performance of Ferry Vessels Operating on the Merak Bakauheni Route - Piere Marcello Lopulalan; Rahmat Santoso; Hendi Prasetyo; Febria Surjaman; Hendra Purnomo (CV. Syntax Corporation Indonesia, 2025)
Fuel consumption remains one of the most significant operational components in the maritime transportation sector, particularly on routes characterized by high vessel frequency such as Merak Bakauheni. This study aims to examine the efficiency of fuel utilization among four ferry vessels operating on this route two categorized as express ferries and two classified as regular ferries. Using a mixed-methods approach that integrates quantitative fuel-use analysis with qualitative evaluation of operational constraints, the research investigates how engine speed, power output, voyage duration, and port-related delays affect overall fuel efficiency. The findings demonstrate substantial differences in fuel consumption between the two ferry categories, largely influenced by engine load patterns and operational behavior. Furthermore, port congestion, limitations in jetty availability, and slow loading unloading procedures contribute significantly to additional fuel usage, particularly through prolonged auxiliary engine operation. These findings emphasize the need for an improved operational framework that includes speed optimization, more effective port coordination, and real-time monitoring mechanisms to minimize fuel waste and enhance maritime performance.